Impact of the Quality of Tourist Attraction and Promotion on Tourist Loyalty with Visiting Decisions as Intervening Variables - Muhammad A'an Auliq; Raden Andi Sularso; Andriyansah Andriyansah; Endi Isnarno (Journal of International Conference Proceedings, 2022)
This study aims to determine the effect of the quality of tourist attractions and promotions on tourist decisions and loyalty as a result of the decline in the number of tourists. The respondents of this study were 100 tourists who visited Ijen Crater in July 2019 both foreign tourists and local tourists. The data analysis technique used structural equation modeling (SEM) Warp PLS 5.0. The results showed that there was a positive and significant influence of tourist attraction on the decision to visit. There is a positive and significant effect of tourism promotion on visiting decisions. There is a positive and significant influence of tourist attraction on tourist loyalty. There is a positive and significant effect of tourism promotion on tourist loyalty. There is a positive and significant influence on the decision to visit on tourist loyalty. Path analysis test results show that there is a positive and significant indirect effect between tourist attraction and tourist loyalty through visiting decisions. And there is a positive and significant indirect effect of tourism promotion on visiting loyalty through visiting decisions.Â Keywords: Quality of tourist attraction, promotion, decision to visit, tourist loyalty